Effect of triisopropanolamine on compressive strength and hydration of cement-fly ash paste. (10th August 2018) - Ma, Baoguo; Zhang, Ting; Tan, Hongbo; Liu, Xiaohai; Mei, Junpeng; Qi, Huahui; Jiang, Wenbin; Zou, Fubing
Highlights: TIPA can increase compressive strength of cement-FA system. TIPA can accelerate the hydration of both cement and FA. TIPA can facilitate the dissolution of FA. Air-entraining effect of TIPA negatively affects compressive strength. Abstract: This paper aims to investigate the effect of triisopropanolamine (TIPA) on compressive strength and hydration of cement-fly ash paste. The samples with various dosages of TIPA were prepared with 30% fly ash (FA) and 70% cement (water/binder ratio by weight = 0.38), and cured under the standard condition. The compressive strength, pore structure, hydration process, and hydration products were investigated. The results show that TIPA can obviously increase the compressive strength of cement-FA system at the age of 7 d and 60 d, and the reasons are involved in pore structure and hydration of cement-FA system. Pore structure was characterized with mercury intrusion porosimetry, and the results show that TIPA can reduce total porosity but increase the amount of pore with size more than 50 nm, implying the air-entraining effect with negative effect on compressive strength. The result suggests that TIPA and defoaming agent should be used together to minimize the negative effect in real concrete. Furthermore, analysis of hydration products shows that TIPA can accelerate the hydration of both cement and FA, and this can also be illustrated from solid-state nuclear magnetic resonance. It is noticed that TIPA can hasten the conversion of AFt to AFm, which can be indicated from hydration heat. Additionally, the acceleration of pozzolanic reaction of FA is because TIPA can accelerate the dissolution of aluminate, silicate, and ferric into liquid paste which was demonstrated from morphology characterization and the change of ions in pore solution. Such results would be expected to provide experience for the use of alkanolamine in promoting the performance of cement-based materials.